Quantum oscillations in the type-II Dirac semi-metal candidate PtSe2 - Yang, Hao; Schmidt, Marcus; Suess, Vicky; Chan, Mun; Balakirev, Fedor F.; Mcdonald, Ross D.; Parkin, Stuart S. P.; Felser, Claudia; Yan, Binghai; Moll, Philip J. W. (New Journal of Physics, 2018)
Three-dimensional topological semi-metals carry quasiparticle states that mimic massless relativistic Dirac fermions, elusive particles that have never been observed in nature. As they appear in the solid body, they are not bound to the usual symmetries of space-time and thus new types of fermionic excitations that explicitly violate Lorentz-invariance have been proposed, the so-called type-II Dirac fermions. We investigate the electronic spectrum of the transition-metal dichalcogenide PtSe2 by means of quantum oscillation measurements in fields up to 65 T. The observed Fermi surfaces agree well with the expectations from band structure calculations, that recently predicted a type-II Dirac node to occur in this material. A hole- and an electron-like Fermi surface dominate the semi-metal at the Fermi level. The quasiparticle mass is significantly enhanced over the bare band mass value, likely by phonon renormalization. Our work is consistent with the existence of type-II Dirac nodes in PtSe2, yet the Dirac node is too far below the Fermi level to support free Dirac-fermion excitations.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Dirac-fermion; Fermi surface; focused ion beam; quantum oscillations; transition-metal dichalcogenide